Pengelolaan Sumber Daya Perikanan Banggai Cardinalfish (Pterapogon kauderni, Koumans 1933) Dengan Pendekatan Ekosistem (Studi Kasus Pulau Banggai Kabupaten Banggai Laut) - Yeldi Adel; . Yonvitner; Muhammad Fadjar Rahardjo (Institut Pertanian Bogor, 2016)
The Banggai cardinalfish (Pterapogon kauderni) is endemic to the Banggai Archipelago. The conservation status of Pterapogon kauderni in the IUCN Red List of Threatened Species is Endangered, Pterapogon kauderni is considered to be threatened with extinction due to excessive exploitation as well as threats to it’s habitat in shallow coastal waters of 0-5 m depth. The aim of this research was to evaluate this fisheries resource using ecosystem-based indicators and to formulate fisheries management measures using an ecosystem-based approach. The six domains used in this evaluation were the fisheries resource domain, habitat and ecosystem, fishing technology, social, economic, and institutional, using a specific set of indicators for each domain. The evaluation produced the following overall, mean, and highest indicator values and domain categories; 3.226.40, 2.33 and 4.204.12 for the fisheries resource domain, poor category; 4.020.80, 2.17, 5.282.36 for the habitat and ecosystem domain, average category; 4.000, 2.00, 6.000 for the fishing technology domain, average category; 6.685, 2.33, 8.505 for the social domain, category; 2.001.74, 1.50 and 3.005.17 for the economic domain, poor category; and 3.041.38, 2.17, 4.564.12 for the institutional domain, average category